A Few Facts About Your Journal - Nko'o Amvene, Samuel (HEALTH SCIENCES AND DISEASE, 2025)
Health Sciences and Disease, is an open source, peer reviewed medical journal that covers all aspects of medicine, pharmacy, biomedical and health sciences, including public health and societal issues. It is an online first publication, which means that all the publications articles appear on the website before being included in the print journal. The papers are published in full on the website, with open access. Our vision is to be the leader medical journal in our region. Our mission is to inform and educate all the health professionals and to promote constructive debate on health issues that matter in the management not only of diseases but of health as a whole. Health Sciences and Disease is the official publication of the Faculty of Medicine and Biomedical Sciences of the University of Yaounde I. Its team is based in Yaounde (Cameroon). Health Research in Africa (HRA) is a partner journal of HSD.